Design and Kinematics Analysis of the R& (2-SPU+PRR) Hybrid Mechanism for Ankle Rehabilitation - Wang Zhihao; Li Ruiqin; Fan Wenlong; Wang Chunzhen (Jixie chuandong)
Aiming at the ankle rehabilitation and training of stroke patients, an ankle rehabilitation mechanism with 3R1T sports performance is proposed. The screw theory is used to analyze the degree of freedom, the closed vector method is used to solve the inverse position solution, and Adams is used to simulate the kinematics of the hybrid mechanism. The maximum rotation angle error of the mechanism during dorsiflexion and toe flexion is calculated. The results show that under the displacement-restriction device, the mechanism can complete the rehabilitation movement and vertical joint traction movement required by patients within the safe range of ankle movement.